Genebanks and market participation: evidence from groundnut farmers in Malawi - Tabe-Ojong, Martin Paul; Smale, M.; Jamora, Nelissa; Azevedo, V.C.R. (Springer, 2022)
Abstract Background Genebanks contribute to poverty reduction as well as food and nutritional security by being one of the main sources of diversity for the development of improved crop varieties. While the welfare implications of adopting improved varieties have been documented in many rural settings, little attention has been placed on genebanks that often supply key traits and genetic diversity to plant breeders by providing seed samples. In this study, we examined the contribution of the genebank housed by the International Crops Research Institute (ICRISAT) to the development of improved groundnut varieties used by farmers in Malawi. We then related this apportioned genebank contribution to market outcomes, such as market participation and the quantity of groundnut sold in markets.